2018
DOI: 10.1136/bcr-2018-225980
|View full text |Cite
|
Sign up to set email alerts
|

Retzius space haematoma as a rare cause of concealed retroperitoneal postpartum haemorrhage following spontaneous vaginal delivery

Abstract: A 34-year-old woman presented to hospital in shock 8 hours after a spontaneous home vaginal delivery. She is a known carrier of haemophilia A. Examination revealed a tender but firm, central and contracted uterus. There was a small second-degree perineal tear which was not actively bleeding and no other trauma or bleeding visualised in the vault or cervix. Bedside ultrasound showed a large 1 L blood clot anterior to the empty uterus. Exploratory laparotomy was performed which revealed a haematoma in the Retziu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…Patients who deteriorate while on conservative management will need immediate surgical exploration [ 1 ]. Most of the patients reported required surgical intervention as they were hemodynamically unstable [ [2] , [3] , [4] , 6 , 7 ] and the source of bleeding needed to be identified and hemostatic sutures applied to stop the bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who deteriorate while on conservative management will need immediate surgical exploration [ 1 ]. Most of the patients reported required surgical intervention as they were hemodynamically unstable [ [2] , [3] , [4] , 6 , 7 ] and the source of bleeding needed to be identified and hemostatic sutures applied to stop the bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…The failure of incision and drainage in three cases, with the need for subsequent transcatheter arterial embolisation (TAE) described by Baruch et al [ 3 ] and Villella et al [ 4 ] and laparotomy in one by Singh et al [ 5 ], highlights the potential difficulties in accessing and achieving haemostasis in this large potential space. Laparotomy and radiologically guided drainage have also been described as primary approaches [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Literature reviews have revealed that the incidence of puerperal hematoma varies from 1:309 to 1:1500 deliveries. 2 Incidents can occur immediately after delivery or during the puerperal period. 3 Puerperal hematomas are mainly located on the vulva, vagina, broad ligament and rarely but possible happen in the retroperitoneal area.…”
Section: Introductionmentioning
confidence: 99%